YouTube for young children: what are infants and toddlers watching on the most popular video-sharing app? - Henderson, Dahlia; Bailes, Talia; Sturza, Julie; Robb, Michael B.; Radesky, Jenny S.; Munzer, Tiffany G. (Frontiers in Developmental Psychology, 2024)
Background: Infants and toddlers engage with digital media about 1-3 hours per day with a growing proportion of time spent on YouTube.Aim: Examined content of YouTube videos viewed by children 0-35.9 months of age and predictors of YouTube content characteristics.We completed a secondary analysis of data from the 2020 Common Sense "YouTube and Kids" study. Parents were surveyed about demographics and YouTube viewing history. We developed a novel coding scheme to characterize educational quality and comprehension-aiding approaches (i.e., labels, pacing) in 426 videos watched by 47 children. Videos were previously coded for violence and consumerism. Bivariate analyses compared video-level predictors of higher quality educational content.Multivariable analyses examined child and family predictors of YouTube video content, adjusted for FDR.Results: Only 19% of videos were age-appropriate, 27% were slow paced, 27% included physical violence, and 48% included consumerism. The game genre was associated with faster pace, more physical violence, more scariness, and more consumerism vs. all other videos. The informational genre was associated with more learning goals, slower pace, and less physical violence vs. all other videos. Child age 0-11.9 months vs. 24-35.9 months was associated with more age-inappropriate and violent content.Conclusions: Physical violence and consumerism were prevalent among YouTube videos viewed by this sample, with infants being exposed to more age-inappropriate and violent content compared with toddlers. Caregivers may wish to select videos in the informational genre which tended to include more high-quality indicators and avoid gaming videos and monitor young infant video content.